Dreaming in Dialogue: A Discussion of "Field Theory and the Dream Sense: Continuing the Comparison of Interpersonal/Relational Theory and Bionian Field Theory". Issue 5 (2nd September 2020) - Colombo, Daria
Abstract : Donnel Stern (this issue) broadens his description of emergence in relational theory to encompass what he defines as a "dream sense, " a concept via which he attempts to translate the oneiric work of BFT into a relational model. Unlike Bionian Field Theory (BFT), Stern's claim on Bion's theory pointedly excludes one of its essential aspects, the asymmetry of the container and the contained. By enlarging his bridge to Bionian concepts, Stern may risk making interpersonal/relational psychoanalysis (IRP) something much closer to BFT indeed, in which the asymmetry Stern rejects is inevitably called back in, or sneaks back in along with the dream and the dream sense.